IMPLEMENTASI DAN IMPLIKASI UU NO. 23 TAHUN 2011 TERHADAP PENGELOLAAN ZAKAT (Studi Pengelolaan Zakat Di BAZNAS Kabupaten Rejang Lebong) - Hafizano, Hafizano (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The study aims to answer  the question of how the role of BAZNAS Rejang Lebong  Regency in  implementing Law no. 23 of 2011 on the collection and distribution of zakat. How is the impact of the implementation of Law no. 23 Year 2011 on the management of zakat ?. And What are the constraints and strategies facing BAZNAS Rejang Lebong Regency in implement- ing the Act on the management of zakat ?. This research  is a qualitative  research  using research  approach, phenomenological, sociological and  historical approach. This research  uses field research  type (field research), that is a research  conducted inten- sive, detailed  and  deeply  to a certain  object.  Data  Collection  Techniques This research  is primary  data  and  secondary data. In accordance with the characteristics  of empirical  legal research   using  secondary  data   as  the   initial  data  obtained  from primary   and  secondary legal materials,  then  continued with primary  data  or field data  obtained from documents, interviews and  observations. The results showed;  First, that the implementation of Law no. 23 Year 2011   in  the  management  of zakat has  run  optimally  in  accordance with  the mandate of the Act. Second, the implications of the implementation of the Law on the management  of zakat  has given a positive effect. Proven  with ZIS  funds received  in 2012-2016 there  is an increase  and ZIS funds have been distributed to mustahiq. Thirdly, the obstacles faced by BAZNAS Rejang Lebong Regency in implementing the Zakat Law are: (a) The absence of sanction  for muzakki not paying zakat, (b) Some people  consider  BAZNAS Kab. Rejang Lebong  is the same  as a community organization, whereas  BAZNAS is the official government institution   regulated  by  law. (C)  There   are   still  many   people   who   are   less concerned about  the obligations  of zakat and  the lack of zakat awareness through  an institution.  (D) Most Dhuafa  ‘consider BAZNAS’s assistance  as consumptive. The Strategy pursued by BAZNAS in the management of zakat are: First, BAZNAS cooperates with Rejang  Lebong  Regency  Government  so  that  it is issued Lo- cal Regulation and Regulation of Bupati. Secondly,  BAZNAS’s effort in managing ZIS is by way of socialization and cooperation with religious leaders  and   community  leaders.   Thirdly,  Mustahiq   who   is  reluctant   to  return   t he productive  zakat funds then for the fund the continuation is not given anymore